Posterior segment manifestations in human immunodeficiency virus/acquired immunodeficiency syndrome patients in rural population of central india - Agrawal, Gaurav; Babber, Meenu; Sami, Ifsa; Sharma, Reena; Ranjan, Ravi (International Journal of Research in Medical Sciences, 2019)
Background: Ocular manifestations of HIV infections are common in the developing countries with lacking data in rural areas. The aim of study was to assess the prevalence of ophthalmic manifestations among HIV infected individuals in rural population and to find the relationship between CD4 count and ocular manifestations among these individuals. Methods: Authors have included 400 HIV patients of age more than 15 years that were registered in ART center of our institute. Ocular examination was done with slit lamp biomicroscope and indirect ophthalmoscope. Blood sample was sent for CD4 count analysis. Results: The mean age of patients ware 31.9±9.3 years, the ocular manifestations were more commonly found in the age group 25-35 years. 51 % were males and 49% were females. Most common mode of transmission was heterosexual contact (51%).55 % patients had CD4 count >150 cell/cumm. Cotton wool spots (36%) and intra-retinal haemorrhages (32%) was most common posterior segment findings followed by ocular toxoplasmosis (13%), CMV retinitis (10%), acute retinal necrosis (3 %). Conclusions: The prevalence of ocular manifestations in HIV patients is high and is a burden for our society, authors recommend screening of all the HIV patients to detect any vision threatening ocular lesions at the earliest.